Triglyceride and Triglyceride/HDL (High Density Lipoprotein) Ratio Predict Major Adverse Cardiovascular Outcomes in Women With Non‐Obstructive Coronary Artery Disease. Issue 9 (7th May 2019) - Prasad, Megha; Sara, Jaskanwal Deep; Widmer, Robert J.; Lennon, Ryan; Lerman, Lilach O.; Lerman, Amir
Abstract : Background: Women with non‐obstructive coronary artery disease have increased cardiovascular morbidity. The role of risk factors in this population has yet to be established. We aimed to study the predictive effect of triglycerides and the triglyceride/high‐density lipoprotein ratio on major adverse cardiovascular events (MACE) in patients with non‐obstructive coronary artery disease, and to explore the role of lipid lowering therapy in modifying this risk. Methods and Results: This is a prospective cohort study enrolling patients with anginal symptoms referred to the cardiac catheterization laboratory for suspected ischemia, who were subsequently diagnosed with non‐obstructive coronary artery disease, defined as no stenosis >20% on angiography. All patients had baseline laboratory testing and were followed for 7.8±4.3 years for the development of major adverse cardiovascular events. We performed Cox proportional hazard testing to determine the effect of triglycerides on risk of major adverse cardiovascular events among men and women by baseline statin use. A total of 462 patients were included. Median age was 53 (Q1, Q3: 45, 62) years. In a Cox proportional hazard model stratified by statin use adjusting for confounders, among those not on baseline statins, triglycerides were independently predictive of major adverse cardiovascular events in women (per 50 mg/dL risk ratio: hazard ratio 1.25 [95% CI: 1.06, 1.47]; P =0.01). This was not true among men. The interaction between triglycerides and sex, and triglycerides and statin was statistically significant. Conclusions: Triglyceride levels may play a key role in predicting cardiovascular‐specific risk in women, and statin use may be protective. Further investigation is necessary to better delineate the role of statin use in preventing cardiovascular risk.